Rapid hemostasis in a sheep model using particles that propel thrombin and tranexamic acid. (10th November 2016) - R. Baylis, James; Finkelstein‐Kulka, Andres; Macias‐Valle, Luis; Manji, Jamil; Lee, Michael; Levchenko, Elina; Okpaleke, Christopher; Al‐Salihi, Salahuddin; Javer, Amin; J. Kastrup, Christian
Abstract : Objectives/Hypothesis: Bleeding during endoscopic sinus surgery and open surgeries can easily obstruct the surgeons' field of view and increase morbidity and risk of intraoperative complications. Intraoperative bleeding could potentially be addressed by a hemostatic agent that safely disperses itself through the escaping blood. We tested the safety and efficacy of a self‐propelling formulation of thrombin and tranexamic acid (SPTT) in stopping bleeding in a paranasal sinus injury and in an open surgical carotid injury sheep model. Study Design: Interventional animal study. Methods: SPTT was tested in the sinonasal space following endoscopic injury to the inferior turbinate of six sheep, and to the common carotid artery following open surgical injury in eight sheep. In the nasal cavity, bleeding time and local inflammation were measured and compared to plain gauze. Following carotid arteriotomy, successful hemostasis and markers of thrombosis and coagulopathy were compared to Floseal. Results: SPTT significantly decreased bleeding times in the sinonasal space compared to plain gauze (mean difference = 3.8 minutes, P = .002). All of the carotid bleeds (100%) were successfully controlled with SPTT after 10 minutes of application under pressure, compared to 25% with Floseal. No adverse events were noted, and there was no evidence of thromboembolism. Conclusions: SPTT significantly reduced bleeding time in a sheep model of surgical sinus bleeding and successfully stopped bleeding following catastrophic carotid artery injury, with no adverse events observed. Level of Evidence: NA Laryngoscope, 127:787–793, 2017